2022
DOI: 10.3389/fonc.2022.1030786
|View full text |Cite
|
Sign up to set email alerts
|

Germline and somatic variants in ovarian carcinoma: A next-generation sequencing (NGS) analysis

Abstract: BackgroundGermline BRCA1/2 mutations are identified in 13-15% of ovarian cancers, while an additional 5-7% of ovarian cancers harbor somatic BRCA1/2 mutations. Beyond these mutations, germline or somatic aberrations in genes of the homologous recombination (HR) pathway such as RAD51B/C/D, PALB2, ATM, BRIP1 may confer an HR deficiency in up to 50% of ovarian tumors. Next-generation sequencing (NGS) is a high-throughput massive parallel sequencing method that enables the simultaneous detection of several mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
(19 reference statements)
1
4
1
Order By: Relevance
“…The prevalence of TP53 somatic variants categorized as non‐functional or likely non‐functional, which may disturb p53 function, was 62.5% (35/56) of all patients, and 64.7% (22/34) of HGSOC patients. The frequency of TP53 somatic variants in the present study was lower than the 68%–96% frequency found in other studies 82–85 . Most TP53 somatic variants found here were missense substitutions spanning exons 5 to 8, which correspond to the DNA‐binding domain (amino acid residues 95–288) 86,87 .…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The prevalence of TP53 somatic variants categorized as non‐functional or likely non‐functional, which may disturb p53 function, was 62.5% (35/56) of all patients, and 64.7% (22/34) of HGSOC patients. The frequency of TP53 somatic variants in the present study was lower than the 68%–96% frequency found in other studies 82–85 . Most TP53 somatic variants found here were missense substitutions spanning exons 5 to 8, which correspond to the DNA‐binding domain (amino acid residues 95–288) 86,87 .…”
Section: Discussioncontrasting
confidence: 74%
“…The frequency of TP53 somatic variants in the present study was lower than the 68%-96% frequency found in other studies. [82][83][84][85] Most TP53 somatic variants found here were missense substitutions spanning exons 5 to 8, which correspond to the DNA-binding domain (amino acid residues 95-288). 86,87 Nineteen of these missense somatic variants are frequently reported in ovarian tumors, occurring at codons considered cancer hotspots, 88,89 and presented VAFadjusted ranging from to 100%.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, figuring out the alterations of BRCA1/2 , especially germline mutation, is an effective way to identify the inherited risk of cancer and take preventive measures. Previous studies showed that about 8.6–24.5 % patients harbored g BRCA1/2 mutations, while 3.7–7.1 % patients presented s BRCA1/2 mutations [ 10 , [31] , [32] , [33] , [34] , [35] ]. Our study excluded the benign mutations and found the frequencies of g/s BRCA1/2 mutation were 18.55 % and 9.68 %.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been observed that those patients presenting germline BRCA1 and BRCA2 pathogenic variants show a better response to platinum-based treatments [ 57 ]. As for the somatic mutations, they are detected in 5–7% of OC cases [ 58 ]. Of note, better short-term survival rates have been observed in those patients carrying BRCA mutations; however, there are some contradictory observations at longer times, with studies reporting conflicting mortality rates for BRCA-mutated carriers vs. noncarriers [ 59 , 60 , 61 ].…”
Section: Biomarkers In Ovarian Cancer: From Diagnosis To Prognosismentioning
confidence: 99%